2012
DOI: 10.3348/kjr.2012.13.5.594
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MRI T2 Relaxation Changes of Knee Articular Cartilage before and after Running between Young and Old Amateur Athletes

Abstract: ObjectiveTo compare changes in T2 relaxation on magnetic resonance (MR) images of knee articular cartilage in younger and older amateur athletes before and after running.Materials and MethodsBy using a 3.0-T MR imager, quantitative T2 maps of weight-bearing femoral and tibial articular cartilages in 10 younger and 10 older amateur athletes were acquired before, immediately after, and 2 hours after 30 minutes of running. Changes in global cartilage T2 signals of the medial and lateral condyles of the femur and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 22 publications
0
35
1
Order By: Relevance
“…Interestingly, these previous studies were all conducted in healthy young individuals (mean age b 30 years). While age has not been found to significantly influence T2 response to running in previous studies [8,26], perhaps a combination of age and running experience could have influenced the current findings. Indeed, the cohort comprised experienced recreational runners (average 12.1 years of experience, running 22.7 km/week).…”
Section: T1ρ Relaxation Time Values (Ms)contrasting
confidence: 61%
“…Interestingly, these previous studies were all conducted in healthy young individuals (mean age b 30 years). While age has not been found to significantly influence T2 response to running in previous studies [8,26], perhaps a combination of age and running experience could have influenced the current findings. Indeed, the cohort comprised experienced recreational runners (average 12.1 years of experience, running 22.7 km/week).…”
Section: T1ρ Relaxation Time Values (Ms)contrasting
confidence: 61%
“…For the assessment of the immediate influence of athletic loading on cartilage relaxation times, only T1rho and T 2 have been applied and investigated so far. 19,20,27 One previous investigation of Subburaj et al 19 The authors observed a slight increase of relaxation times immediately after the run, but they returned to approximately prerun values after 2 h. As an explanation, the authors argue that they analyzed actual running in an in vivo study design instead of passive knee bending. These findings are contrary to our results and to the above-mentioned publications, although the study designs are comparable.…”
Section: Discussionmentioning
confidence: 95%
“…17,18 T1rho and T 2 have also proven to be reliable in the detection of acute effects on the articular cartilage of the knee after physical loading. 19,20 To the best of our knowledge, no comparison of the immediate effects on T 2 and T 2 * relaxation times after running has been published. Hence, the purpose of the presented feasibility study was to analyze the acute effects of long-distance running on T 2 and T 2 * relaxation times in young, active adults and to investigate the correlation between these two biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Using magnetic resonance imaging (MRI) -a reliable in vivo method for noninvasive morphological and qualitative assessment of knee cartilage [16][17][18][19][20] -specific volume and thickness (height: Ht) measurement methods with high levels of precision and reproducibility [21][22][23][24][25], as well as post-race T1rho-and T2-relaxation time mapping, have been performed to quantify structure and composition changes in hyaline cartilage on short (5 km) up to long-distance running (marathon) [26][27][28][29][30][31][32][33][34][35]. Both mapping techniques are sensitive to collagen fiber content and network, and to a lesser extent to proteoglycan (PG) changes, showing a high negative correlation with their chondral concentration [36,37], with T2-measurements additionally sensitive to changes of intrachrondral free water content [38].…”
Section: Introductionmentioning
confidence: 99%